Typification of Gagea lacaitae (Liliaceae) revisited - Ferrer-Gallego, P. Pablo (Phytotaxa, 2023)
The typification of the name Gagea lacaitae (Liliaceae) is revised. A lectotypification had previously been proposed by Peruzzi and Tison in 2004 from a specimen kept at NAP (Herbarium A. Terracciano, now with barcode NAP0001973) and collected by Parlatore in 1848. However, Terracciano cited in the protologue gatherings collected by Juan Isern and Gaetano Leone Durando. Specimens of these gatherings are kept at NAP, MA, P, and PAL. Therefore, this material has preference in the lectotype designation and must be chosen according to the International Code of Nomenclature for algae, fungi, and plants (Art. 9.12 of the Shenzhen Code of 2018).